Perioperative fluid management for major elective surgery. Issue 2 (5th January 2020) - Heming, N.; Moine, P.; Coscas, R.; Annane, D.
Abstract : Background: Adequate fluid balance before, during and after surgery may reduce morbidity. This review examines current concepts surrounding fluid management in major elective surgery. Method: A narrative review was undertaken following a PubMed search for English language reports published before July 2019 using the terms 'surgery', 'fluids', 'fluid therapy', 'colloids', 'crystalloids', 'albumin', 'starch', 'saline', 'gelatin' and 'goal directed therapy'. Additional reports were identified by examining the reference lists of selected articles. Results: Fluid therapy is a cornerstone of the haemodynamic management of patients undergoing major elective surgery. Both fluid overload and hypovolaemia are deleterious during the perioperative phase. Zero‐balance fluid therapy should be aimed for. In high‐risk patients, individualized haemodynamic management should be titrated through the use of goal‐directed therapy. The optimal type of fluid to be administered during major surgery remains to be determined. Conclusion: Perioperative fluid management is a key challenge during major surgery. Individualized volume optimization by means of goal‐directed therapy is warranted during high‐risk surgery. In most patients, balanced crystalloids are the first choice of fluids to be used in the operating theatre. Additional research on the optimal type of fluid for use during major surgery is needed. Abstract : This review highlights current knowledge related to perioperative fluid management for major elective surgery. Volume optimization through goal‐directed therapy during high‐risk surgery is warranted. Balanced crystalloids are generally the first choice of fluids during major elective surgery. Additional research regarding perioperative fluid management is needed. Goal is zero fluid balance A video abstract is available at https://youtu.be/bpGfABtVzdQ Abstract : Antecedentes: Un equilibrio de líquido adecuado antes, durante y después de la cirugía puede reducir la morbilidad. Esta revisión presenta los conceptos actuales del manejo de líquidos en cirugía mayor electiva. Métodos: Se realizó una revisión descriptiva tras llevar a cabo una búsqueda en PubMed de artículos publicados en inglés antes de julio 2019, utilizando los términos 'cirugía ' ( surgery ), 'líquidos' ( fluids ), `fluidoterapia` ( fluid therapy ), 'coloides' ( colloids ), 'cristaloides' ( crystalloids ), 'albúmina' ( albumin ), 'hidroxietil‐almidón' ( starch ), 'salino' ( saline ), 'gelatina' ( gelatin ) y 'terapia dirigida por objetivo' ( goald directed therapy ). Se identificaron artículos adicionales a través de la lista de referencias bibliográficas de los artículos seleccionados. Resultados: El tratamiento con líquidos constituye la piedra angular del manejo hemodinámico de los pacientes sometidos a cirugía mayor electiva. Tanto la sobrecarga de líquidos como la hipovolemia son perjudiciales durante el periodo perioperatorio. El tratamiento de líquidos con balance cero debe considerarse el objetivo. En pacientes de alto riesgo, el manejo hemodinámico personalizado se debe ajustar mediante la utilización del tratamiento dirigido por objetivos. El tipo óptimo de líquido que debe ser administrado durante la cirugía mayor todavía no se ha determinado. Conclusión: El manejo perioperatorio de líquidos es un desafío clave durante la cirugía mayor. La optimización del volumen individualizado a través de un tratamiento dirigido por objetivos está justificada durante la cirugía de alto riesgo. En la mayoría de los casos, la administración equilibrada de cristaloides es la primera fluidoterapia de elección en el quirófano. Se necesitan más investigaciones sobre el tipo de líquidos más adecuado para utilizar durante la cirugía mayor.